The Labour Market for Uber Drivers in Australia. (7th February 2022) - Alexander, Oliver; Borland, Jeff; Charlton, Andrew; Singh, Amit
Abstract: We describe the labour market for Uber drivers, the first detailed study of a gig economy market in Australia. Uber drivers' characteristics, reasons for driving with Uber, hours of work and driving schedules, earnings and job satisfaction are analysed, using both administrative and survey data. Uber drivers have diverse pathways to the job, with the objective to earn supplemental income most important in Australia. Total hours and timing of work differ substantially between drivers. Drivers express high satisfaction regarding job flexibility but lower satisfaction about pay. Hours worked and job satisfaction depend importantly on a driver's pathway to the job.